PassiveTeX: from XML to PDF - Goossens, M; Rahtz, S (TeX Users Group, 2000)
This article introduces Passive TeX, a library of TeX macros based on xmltex, that processes XML documents containing XSL formatting objects and generates PDF or DVI output. We show examples of typesetting XML sources marked up using the TEI, DocBook, and MathML DTDs.